The transcript expression of pluripotent genes in bovine embryonic stem like cells - Long, Le Thanh; Phuong Thao, Nguyen Thi; Chung, Doan Chinh; Sy, Do Minh; Trinh, Le Huu; Son, Hoang Nghia (Academia Journal of Biology, 2015)
In this study, the bovine embryonic stem like cells were isolated and cultured from blastocyst stage embryos. The bovine embryonic stem like cells were cultured on the feeder cells which were 10 µg/ml mitomycin C-inactivated mouse embryonic fibroblasts. The real time qRT-PCR was applied to estimate the pluripotent gene expression of bovine embryonic stem like cells. The bovine embryonic stem like cell colonies were positive to alkaline phosphatase. However, the alkaline phosphatase expression of bovine embryonic stem like cells was down regulated in third passage. The result of relative quantification of pluripotent gene transcripts showed that the oct4 transcripts expression in third passage was higher than the first and the second passages. The nanog and sox-2 transcript expression in bovine embryonic stem like cells were down regulated during passages, especially, the sox-2 transcript expression in the third passage was dramatically down regulated than the fisrt passage (10 times lower). The c-myc transcript expression of bovine embryonic stem like cells in the third passage was higher than the first and the second passages. The transcript expression modification of pluripotent genes including oct4, nanog and sox-2 were related to the morphological changes of bovine embryonic stem like cells including flat and irregular sharp which were characteristics of differentiation of embryonic stem like cell colonies.